Dampak Sosial dan Ekonomi dari Pengembangan Kawasan Agrowisata: Studi di Desa Serang, Kabupaten Purbalingga - Nindhia Lupita Wardhani; I Made Krisnajaya; Danang Wahansa Sugiarto (AGRIMOR, 2023)
Currently, agrotourism is growing rapidly in Central Java, one of which is Serang Village Agrotourism. The development of agrotourism is considered to have an impact on the community, both in terms of the economy and social life. The purpose of this research is to describe the various impact that arise, both from economic and social aspects, from the development of the agrotourism area of Serang Village in Purbalingga Regency. The research method used is a qualitative-descriptive research method, with a case study approach. The data collected included the results of interviews with predetermined informants (purposive sampling) as well as from observation. In addition, data from official websites, news articles, and related institutional documents are also used. The results of this study show that there are positive and negative impacts arising from the development of agrotourism areas in Serang Village, both from economic and social aspects. The positive impact of the development of agrotourism is an increase in income and the development of open and creative mindset in the community. A better understanding of education, a thriving lifestyle, and increased business opportunities have also had a positive impact on society. The negative impacts that arise include the presence of sufficiently increased noise and the emergence of air pollution. Apart from that, there was another negative impact, namely the large amount of land owned by local people was sold to people outside Serang Village.